Spatial Localization of Biosensor Fluorescence Signals in Human Skin under the Effect of Equalization of the Refractive Index of the Surrounding Medium. - Meglinski, I. V.; Churmakov, D. Y. (Springer Science Business Media, 2004)
A priority line of biomedical applications of optics is the development of noninvasive diagnostic methods based on the scanning of fluorescence radiation of biosensors embedded in biological tissue. Their main advantage is a high sensitivity and selectivity with respect to given parameters of tissues and their variations. In this study, we present a method for and results of modeling of excitation and propagation of fluorescence radiation in a multilayer randomly inhomogeneous highly scattering and absorbing medium imitating human skin. The model takes into account the spatially inhomogeneous distribution of skin fluorophores and their photophysical characteristics. Both the spatial distribution of fluorescence of skin tissues and the possibility of localization of a detected fluorescence signal are studied. The spatial distribution of fluorescence centers (fluorophores) in the medium is assumed to closely follow the spatial distribution of collagen fibers of the skin. The equalization of the refractive indices at the air–skin interface is shown to lead to a higher degree of localization of the fluorescence signal detected from a biosensor located in a near-surface skin laye